Implementation of Cloud Computing Using the Roadmap for Cloud Computing Adoption (ROCCA) Method in Non-Ministry Government Institutions (Case Study of Lembaga Ilmu Pengetahuan Indonesia) - Haryanto, Tony (PINISI Discretion Review, 2019)
Cloud computing answers some of the challenges in the ICT world, including the high investment that must be spent. This study aims to examine the adoption of the Roadmap for Cloud Computing Adoption model used for cloud computing implementation at the Indonesian Institute of Sciences. This research model uses cloud computing analysis along with each phase of ROCCA and compared with conditions in Non-Ministry Government Institutions (LPNK). The results of this study are a modification of the adoption model of ROCCA, which consists of 5 (five) stages, namely the Analysis, Design, Adoption, Migration, and Management stages. Then it resulted in the implementation of cloud computing with the implementation model of Private Cloud as a service and Infrastructure as a Service service for research institutions at the Indonesian Institute of Sciences. The implementation of cloud computing at LIPI can run well